Defense-related responses in mango (Mangifera indica L.) cultivars ‘Prior’ and‘Kensington’ differing in resistance to Colletotrichum asianum - Supriya, M L; Rakhonde, Gaurav Y; Sriram, S (Journal of Horticultural Sciences, 2026)
Mango is highly susceptible to anthracnose, a major postharvest disease caused by Colletotrichum spp. This study investigated the biochemical mechanisms underlying resistance in two contrasting cultivars, ‘Prior’ (moderately resistant) and ‘Kensington’ (susceptible), following inoculation with Colletotrichum asianum. ‘Prior’ exhibited significantly smaller lesion sizes compared to ‘Kensington’, indicating reduced disease severity. Higher activities of chitinase and -1, 3 glucanase were observed in ‘Prior’, suggesting their critical role in degrading fungal cell walls and conferring resistance. In contrast, elevated polyphenol oxidase and peroxidase were observed in ‘Kensington’, potentially reflecting a weaker or delayed defense response. No significant differences were noted in phenylalanine ammonia lyase and superoxide dismutase activities between the cultivars. Two-way ANOVA revealed significant temporal effects for most enzymes, with genotype×time interactions for chitinase and -1,3-glucanase. Correlation analysis showed co-regulation of these enzymes (r=0.70) and a negative association with PPO (r = -0.85). Principal component analysis (72.90% variance) clearly separated the two cultivars and reflected distinct temporal defense patterns. These findings demonstrate genotype-specific, timedependent regulation of hydrolytic and oxidative defenses, providing a basis for breeding anthracnose-resistant mango cultivars.